The Environment Characteristics Habitat of Sea Tuntong's (Batagur borneoensis) on Conservation Areas in Aceh Tamiang Regency's Coastal Waters - Lubis, Adelia Maisyaroh; Jayanthi, Sri; Setyoko, Setyoko; Fitria, Dini; Munte, Aini; Latif, Danu Abian; Junaidi, Muhammad; Muhaiminin, Haikal (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
One of the endemic turtle conservation areas is the sea turtle conservation area on the coast of Aceh Tamiang Regency, Aceh Province (Batagur borneoensis). This animal is categorized as an endangered animals. The IUCN (International Union for Conservation of Nature and Natural Resources) designated sea turtles as Critically Endangered (CE) in 1996. The distribution of sea turtles is limited because the beach type must be suitable for spawning and survival. The goal of this study was to determine the physical, chemical, and biological characteristics of sea tuntong (Batagur borneonsis) habitat in a conservation area in Aceh Tamiang Regency. In this study, the descriptive method was used. The data collection process was completed. Data was gathered through direct observation in the field. Purposive sampling was used to identify observation stations. There are three research stations: Pusong Kapal (hatching hatchlings), Ujung Tamiang Beach (habitat for adult sea turtles), and Pusung Cium Beach (habitat for sea turtles) (nesting habitat). The study's findings revealed differences in physical, biological, and chemical characteristics at the three stations. It is possible to conclude that the water area off the coast of Aceh Tamiang Regency, Aceh Province, is suitable for sea turtle habitat (Batagur borneoensis)